Economic and Ecological Sustainability in Sustainable Development Planning: An Ecological Economics Approach - Loso Judijanto; Tharienna Dhesta Kusuma Dewi (Nomico, 2026)
This study examines the integration of economic and ecological sustainability in sustainable development planning through the lens of ecological economics. Conventional development planning has historically prioritized economic growth, often neglecting ecological limits and resulting in systemic environmental degradation. Using a qualitative conceptual–normative approach, this research analyzes theoretical foundations, normative principles, and policy implications of ecological economics as an alternative development paradigm. The study draws on an in-depth review of classical and contemporary literature on sustainable development, ecological economics, and environmental policy. The findings indicate that ecological economics provides a more comprehensive framework for development planning by recognizing the economy as a subsystem of the ecosystem, emphasizing sustainable scale, equitable distribution, and ethical governance. This approach challenges growth-centered planning models and offers normative guidance for integrating ecological constraints into policy design. The study concludes that sustainable development planning requires a paradigm shift toward ecological economics to ensure long-term economic viability, environmental integrity, and social justice.